PROXIMATE COMPOSITION AND SIZE RELATIONSHIP IN Parachanna obscura, (Gunter 1861) OF THE CROSS RIVER, NIGERIA - AMA-ABASI, D.; UDO, V.; OKON, S. U. (Nigerian Journal of Fisheries, 2012)
The aquaculture of African snakehead, Parachanna obscura, is gaining an increasing recognition, yet the proximate composition of the species is not known. Study was conducted to determine the proximate composition and their relationship with size of Parachanna obscura, from the Cross River, Nigeria. Ten specimens of Parachanna obscura were analyzed for moisture, protein, fat and crude fibre contents. Mean values for protein, fat and moisture were 18.11, 15.36, and 68.54 %, respectively. There was a direct correlation between protein and the size of the fish (p ≤ 0.01, r = 0.97, n = 10). The relationship was defined by the linear equation y= 6.215 + 0.0872(x). Similarly there was a linear correlation between the fat contents and size (p ≤ 0.05, r = 0.95, n=10). The linear relationship was defined by the equation y=10.38 + 0.367(x). There was ontogenetic shift in protein-fat ratio. The linear relationship between the protein and fats and the weight of the species means that the wet weight of the fish can be used to determine the percentage of protein and fats in the fish without the expensive, laborious and cumbersome method of proximate analysis. The ontogenetic shift in protein–fat ratio implies that people with energy related–health problems can choose between the young and older individuals of Parachanna obscura to meet their specific health challenges.